Pengembangan GEULIS: Prototipe Gelang Emergensi Lansia sebagai Upaya Peningkatan Keamanan Lansia Hidup Sendiri: Indonesia - Rahmawati, Riana; Ahnaf, Kern Cesarean; Pudail, Muhammad (UII, 2025)
The growing elderly population in Indonesia highlights the need for support systems that can ensure their safety and well-being, particularly for those living alone. Living independently increases the vulnerability of older adults to risks such as falls, sudden illness, and emergency conditions that require immediate assistance. However, the use of simple, elderly-friendly emergency technologies at the community level remains limited. This community service program in Purbayan village in Yogyakarta City initiated the development of the Emergency Bracelet for the Elderly Living Alone (GEULIS), an innovative solution based on Internet of Things (IoT) technology. The prototype bracelet was designed with a simple emergency push button system capable of sending alerts via WhatsApp to family members or community health workers, when the elderly require help. The program comprised need assessments, designing and developing the prototype, and pilot testing with elderly individuals living alone. The results demonstrated that the device functioned effectively in transmitting emergency signals. While the design was relatively wearable and user-friendly, further refinement is needed to optimize ease of use. This program highlights the potential for continued development and broader application of GEULIS within the community.